Sustainable Cultural Transformations in Asia: Vietnamese Students’ Intercultural Awareness Following a Malaysian Exchange Programme - Pung, Wun Chiew; Connie Lim, Keh Nie; Ting, Su Hie (Springer Nature Switzerland AG, 2026)
This empirical study examined the impact of a short-term student exchange programme on Vietnamese students’ intercultural awareness, positioning it within the context of growing global interconnectedness. The goal of this chapter is to show how experiential learning through study abroad initiatives can foster intercultural sensitivity, particularly within the As methodology was adopted, using an online questionnaire administered to 104 Vietnamese students who participated in an exchange programme at Universiti Malaysia Sarawak. The questionnaire examined the students’ exposure to other cultures in their family and among friends, and communicative behaviours and attitudes towards other cultures. Key findings indicated that despite limited prior intercultural contact, participants experienced positive shifts in cultural perception and increased ethnorelativism, though they encountered challenges such as adjusting to local cuisine. These results show that even brief study abroad experiences can enhance students’ appreciation for diverse worldviews, values and beliefs. The study suggests that formal intercultural education is essential to prepare students to engage constructively with cultural differences, an increasingly vital skill in a globally connected world.